Pengaruh Independensi, Kompetensi dan Skeptisme Profesional terhadap Kemampuan Auditor dalam Mendeteksi Kecurangan dengan Pelatihan Audit Kecurangan sebagai Variabel Moderasi - Julio Herdi Peuranda; Amir Hasan; Alfiati Silfi (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2019)
This study aims to prove effect of independence, competence and professional skepticism on the auditor’s ability to detect fraud with fraud audit training as a moderating variable. This study on the inspectorate in Riau Province and the survey research using census method, whereas the spreading technique using a questionnaire distributed to inspectors of the Inspectorate, population in this study is the auditor who works at the office inspectorate, 88 questionnaires distributed, a total of 76 questionnaires were returned. Data was analyzed using multiple linear regression testing and MRA. The results of this study indicated that Competence and Professional Skepticism have an effect toward the auditor’s ability to detect Fraud, while Independence didn’t have an effect toward the auditor’s ability to detect fraud. Fraud Audit Training also proved incapable of effect relations on Independence and Competence toward the auditor’s ability to detect fraud, while fraud audit training proved capable of effecting relations on Professional Skepticism toward the auditor’s ability to detect fraud.